Colonic Ischemia Following Major Vascular Surgery: A Literature Review on Pathogenesis, Diagnosis, and Preventive Strategies - Federica Ruggiero; Giulia Colonna; Maurizio Taurino; Elisa Romano; Pasqualino Sirignano (Applied Sciences)
Colonic ischemia (CI) is a serious and potentially fatal complication after major abdominal vascular surgery. This literature review explores the pathogenesis, risk factors, diagnostic methods, and preventive strategies associated with CI, emphasizing the differences between emergency and elective treatments. Early diagnosis through clinical signs and instrumental diagnostics, such as sigmoidoscopy and computed tomography, is crucial. Preventive measures, including preoperative evaluation and perioperative management, are emphasized to reduce the incidence of CI. The results of different studies suggest that endovascular aneurysm repair (EVAR), both emergency and elective, has lower risks of ischemic complications than open surgical repair (OSR), as well as better survival for patients. Further research and standardized clinical guidelines are needed to improve patient outcomes and minimize CI severity.